Characterization of Hair Cell-Like Cells Converted From Supporting Cells After Notch Inhibition in Cultures of the Organ of Corti From Neonatal Gerbils - Li, Yi; Jia, Shuping; Liu, Huizhan; Tateya, Tomoko; Guo, Weiwei; Yang, Shiming; Beisel, Kirk W.; He, David Z. Z. (Frontiers in Cellular Neuroscience, 2018)
The senses of hearing and balance depend upon hair cells, the sensory receptors of the inner ear. Hair cells transduce mechanical stimuli into electrical activity. Loss of hair cells as a result of aging or exposure to noise and ototoxic drugs is the major cause of noncongenital hearing and balance deficits. In the ear of non-mammals, lost hair cells can spontaneously be replaced by production of new hair cells from conversion of supporting cells. Although supporting cells in adult mammals have lost that capability, neonatal supporting cells are able to convert to hair cells after inhibition of Notch signaling. We questioned whether Notch inhibition is sufficient to convert supporting cells to functional hair cells using electrophysiology and electron microscopy. We showed that pharmacological inhibition of the canonical Notch pathway in the cultured organ of Corti prepared from neonatal gerbils induced stereocilia formation in supporting cells (defined as hair cell-like cells or HCLCs) and supernumerary stereocilia in hair cells. The newly emerged stereocilia bundles of HCLCs were functional, i.e., able to respond to mechanical stimulation with mechanotransduction (MET) current. Transmission electron microscopy (TEM) showed that HCLCs converted from pillar cells maintained the pillar cell shape and that subsurface cisternae, normally observed underneath the cytoskeleton in outer hair cells (OHCs), was not present in Deiters’ cells-derived HCLCs. Voltage-clamp recordings showed that whole-cell currents from Deiters’ cells-derived HCLCs retained the same kinetics and magnitude seen in normal Deiters’ cells and that nonlinear capacitance (NLC), an electrical hallmark of OHC electromotility, was not detected from any HCLCs measured. Taken together, these results suggest that while Notch inhibition is sufficient for promoting stereocilia bundle formation, it is insufficient to convert neonatal supporting cells to mature hair cells. The fact that Notch inhibition led to stereocilia formation in supporting cells and supernumerary stereocilia in existing hair cells appears to suggest that Notch signaling may regulate stereocilia formation and stability during development.